Oxidization of optic atrophy 1 cysteines occurs during heart ischemia-reperfusion and amplifies cell death by oxidative stress - Semenzato, Martina; Kohr, Mark J; Quirin, Charlotte; Menabò, Roberta; Alanova, Petra; Alan, Lukas; Pellattiero, Anna; Murphy, Elizabeth; Di Lisa, Fabio; Scorrano, Luca (Redox biology, 2023)
During cardiac ischemia-reperfusion, excess reactive oxygen species can damage mitochondrial, cellular and organ function. Here we show that cysteine oxidation of the mitochondrial protein Opa1 contributes to mitochondrial damage and cell death caused by oxidative stress. Oxy-proteomics of ischemic-reperfused hearts reveal oxidation of the C-terminal C786 of Opa1 and treatment of perfused mouse hearts, adult cardiomyocytes, and fibroblasts with H2O2 leads to the formation of a reduction-sensitive ∼180 KDa Opa1 complex, distinct from the ∼270 KDa one antagonizing cristae remodeling. This Opa1 oxidation process is curtailed by mutation of C786 and of the other 3 Cys residues of its C-terminal domain (Opa1TetraCys). When reintroduced in Opa1-/- cells, Opa1TetraCys is not efficiently processed into short Opa1TetraCys and hence fails to fuse mitochondria. Unexpectedly, Opa1TetraCys restores mitochondrial ultrastructure in Opa1-/- cells and protects them from H2O2-induced mitochondrial depolarization, cristae remodeling, cytochrome c release and cell death. Thus, preventing the Opa1 oxidation occurring during cardiac ischemia-reperfusion reduces mitochondrial damage and cell death induced by oxidative stress independent of mitochondrial fusion.
Keywords: buněčná smrt; Cell Death; autozomálně dominantně dědičná optická atrofie; myši; reperfuzní poškození myokardu; Coronary Artery Disease; Cysteine; Myocardial Reperfusion Injury; peroxid vodíku; zvířata; oxidační stres; Mice; Oxidative Stress; cystein; Optic Atrophy, Autosomal Dominant; Hydrogen Peroxide; nemoci koronárních tepen; Animals